The Effect Of Asset Level On Financial Tax Expense Performance At BRI Bank - Rahmatika, Arivatu Ni’mati; sarjono, amanatus salamah (JURNAL SINTAK, 2025)
This research aims to determine the level of tax assets on the performance of tax burden at Bank BRI. Overall, this research shows that although Bank BRI's profitability has increased in several respects, liquidity must be improved and risks related to solvency reduced. These findings provide valuable insights for bank management in evaluating financial performance and taking strategic steps for future improvement. In addition, this research shows how important effective financial management is to maintain investor and customer confidence and to ensure bank financial sustainability and stability amidst increasing economic challenges. The data used is secondary data from the financial reports of Bank Rakyat Indonesia. The research method used is multiple linear regression with the help of IBM SPSS Statistics 26 software.